Study of Leading Products to Map the Potential of Agribusiness For Tourism Development in the City of Banjarmasin - Normelani, Ellyn; Rusdiansyah, Rusdiansyah; Normasari, Eka Rahayu; Zakiati, Miftahani; Maulida, Emmy; Mursyidah, Annisa (Universitas Lambung Mangkurat, 2023)
The study aims to map the potential of superior agribusiness products for tourism development in Banjarmasin City. The research method is quantitative descriptive using secondary data obtained from BPS South Kalimantan Province and Banjarmasin City. The analysis technique identifies the internal potential of a region, namely basic sectors and non-basic sectors. The potential for agribusiness in the Food Crop Agriculture Sub Sector in Banjarmasin City which can become a base for food crop commodities is the South Banjarmasin District and the North Banjarmasin District. The potential for agribusiness in the Livestock Sub Sector in Banjarmasin City which can be the basis for the livestock sub-sector is the District of South Banjarmasin and Central Banjarmasin. The Fisheries Sub Sector in Banjarmasin City which can be the basis for the livestock sub sector is the North Banjarmasin District and the East Banjarmasin District. The results of research on agribusiness potential in Banjarmasin City seen from the Food Crop Agriculture Sub-Sector include rice, Siamese oranges, and bananas. The agribusiness potential of the Livestock Sub-Sector includes beef cattle, broiler chickens, laying hens, ducks, quail, goats, and free-range chickens. The Fisheries Sub-Sector includes: capture fisheries and freshwater floating net cultivation fisheries, capture fisheries, and still water pond cultivation fisheries.